Community watershed management in semi-arid India: The state of collective action and its effects on natural resources and rural livelihoods - Shiferaw, Bekele A.; Kebede, Tewodros A.; Ratna Reddy, V. (International Food Policy Research Institute, 2008)
Spatial and temporal attributes of watersheds and the associated market failures that accelerate degradation of agricultural and environmental resources require innovative institutional arrangements for coordinating use and management of resources. Effective collective action (CA) allows smallholder farmers to jointly invest in management practices that provide collective benefits in terms of economic and sustainability gains. The Government of India takes integrated watershed management (IWM) as a key strategy for improving productivity and livelihoods in the rain-fed and drought-prone regions. This study investigates the institutional and policy issues that limit effective participation of people in community watershed programs and identifies key determinants for the degree of CA and its effectiveness in achieving economic and environmental outcomes. We use empirical data from a survey of 87 watershed communities in semi-arid Indian villages to identify a set of indicators of CA and its performance in attaining desired outcomes. Factor analysis is used to develop aggregate indices of CA and its effectiveness. Regression methods are then employed to test the effects of certain policy relevant variables and to determine the potential effects of CA in achieving desired poverty reduction and resource improvement outcomes. We find a positive and highly significant effect of CA on natural resource investments, but no evidence of its effects on household assets and poverty reduction outcomes. This may be attributable to longer gestation periods for realizing indirect effects from collective natural resource investments and the lack of institutional mechanisms to ensure equitable distribution of such gains across the community, including the landless and marginal farmers.